Long-term exposure to ambient air pollution and metabolic syndrome in children and adolescents: A national cross-sectional study in China. (March 2021) - Zhang, Jing-Shu; Gui, Zhao-Huan; Zou, Zhi-Yong; Yang, Bo-Yi; Ma, Jun; Jing, Jin; Wang, Hai-Jun; Luo, Jia-You; Zhang, Xin; Luo, Chun-Yan; Wang, Hong; Zhao, Hai-Ping; et al.
Highlights: Few studies have explored the effects of air pollution on metabolic syndrome (MetS) in children. We studied 9, 897 Chinese children in a national cross-sectional study. Long-term exposures to PM2.5, PM10, and NO2 were positively associated with MetS. PM1 and NO2 were related to elevated risk of fasting blood glucose and abdominal obesity. Abstract: Background: The prevalence of metabolic syndrome (MetS) rapidly increased over the past decades. However, little evidence exists about the effects of long-term exposure to ambient air pollution on MetS in children and adolescents. Objective: This study aims to assess the association between long-term ambient air pollution and the prevalence of MetS in a large population of Chinese children and adolescents. Methods: In 2013, a total of 9, 897 children and adolescents aged 10 to 18 years were recruited from seven provinces/municipalities in China. MetS was defined based on the recommendation by the International Diabetes Federation (IDF). Satellite based spatio-temporal models were used to estimate exposure to ambient air pollution (including particles with diameters ≤1.0 µm (PM1 ), ≤2.5 µm (PM2.5 ), and ≤10 µm (PM10 ), and nitrogen dioxide (NO2 )). Individual exposure was calculated according to 94 schools addresses. After adjustment for a range of covariates, generalized linear mixed-effects models were utilized to evaluate the associations between air pollutants and the prevalence of MetS and its components. In addition, several stratified analyses were examined according to sex, weight status, outdoor physical activity time, and sugar-sweetened beverages (SSBs) intake. Results: The prevalence of MetS was 2.8%. The odds ratio of MetS associated with a 10 μg/m 3 increase in PM1, PM2.5, PM10 and NO2 was 1.20 (95%CI: 0.99, 1.46), 1.31 (95%CI: 1.05, 1.64), 1.32 (95%CI: 1.08, 1.62), and 1.33 (95%CI: 1.03, 1.72), respectively. Regarding the MetS components, we observed associations between all pollutants and abdominal obesity. In addition, long-term PM1 and NO2 exposures were associated with the prevalence of elevated fasting blood glucose. Stratified analyses detected that the associations between air pollutants and the prevalence of MetS were stronger in boys ( P interaction < 0.05). Conclusions: We found that long-term exposure to PM2.5, PM10, and NO2 were positively associated with the prevalence of MetS in children and adolescents. Our findings may have certain public health implications for some comprehensive strategy of environment improvement and lifestyles changes in order to reduce the burden of non-communicable disease.